1983
DOI: 10.1007/bf00673708
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory chain of bacterial membrane: assembly-mobile carriers equilibrium

Abstract: The target size of NADH-oxidase activity of M. lysodeikticus isolated membranes for electron radiation is nearly equal to that obtained for NADH-dehydrogenase (about 50 kD). The complete cross-linking of membrane proteins by glutaraldehyde causes an increase of NADH-oxidase target size to 3-3.5 times its original value. Electrons are transported by cross-linked respiratory chain from NADH to O2 with 60-50% effectiveness of that in untreated membranes. It is proposed that electrons are transported through a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…35 The concentrations of coenzymes (NADH and F 420) that directly exchange electrons with respiration chains were detected to investigate whether the respiratory enzymes were electrically stimulated by the DMF (Figure 8). For NADH that donates electrons to the respiratory enzymes to form NAD + , 48,50 the NADH/NAD + ratio was much lower in the DMF group (0.74 vs 1.45 in the control). The lower NADH/NAD + ratio indicated that more electrons were transferred from NADH to form NAD + ; NADH, as an electron carrier, donates electrons to Complex I in the respiratory chain, which is reported to occur in a PCET pattern.…”
Section: Accelerated Electron Transfer In Respiration Chains Benefite...mentioning
confidence: 90%
“…35 The concentrations of coenzymes (NADH and F 420) that directly exchange electrons with respiration chains were detected to investigate whether the respiratory enzymes were electrically stimulated by the DMF (Figure 8). For NADH that donates electrons to the respiratory enzymes to form NAD + , 48,50 the NADH/NAD + ratio was much lower in the DMF group (0.74 vs 1.45 in the control). The lower NADH/NAD + ratio indicated that more electrons were transferred from NADH to form NAD + ; NADH, as an electron carrier, donates electrons to Complex I in the respiratory chain, which is reported to occur in a PCET pattern.…”
Section: Accelerated Electron Transfer In Respiration Chains Benefite...mentioning
confidence: 90%